Control of nuclearity in heterometallic CuII–MnII complexes derived from asymmetric Schiff bases: structures and magnetic properties. Issue 10 (13th February 2018) - Mahapatra, Prithwish; Giri, Sanjib; Drew, Michael G. B.; Ghosh, Ashutosh
Abstract : Among three asymmetric Schiff bases used for the synthesis of heterometallic Cu II –Mn II complexes, the one with N2 O2 donor atoms yielded a tetranuclear and a trinuclear complex whereas two N2 O3 donor ligands produced solely dinuclear complexes. The results of magnetic measurements have been justified by DFT study. Abstract : Two new N2 O3 donor ligands N -(3-methoxysalicylidene)- N ′-(salicylidene)-1, 3-propanediamine (H2 L 2 ) and N -(3-methoxysalicylidene)- N ′-(α-methylsalicylidene)-1, 3-propanediamine (H2 L 3 ) and their Cu(ii ) complexes have been synthesized. Using these complexes and another Cu-complex with one asymmetric N2 O2 donor ligand N -(α-methylsalicylidene)- N ′-(salicylidene)-1, 3-propanediamine (H2 L 1 ) as metalloligands, four new heterometallic Cu(ii )–Mn(ii ) complexes [(CuL 1 )2 Mn2 Cl4 ]·3CH3 OH (1 ), [(CuL 1 )2 MnCl2 ]·2CH3 CN (2 ), [CuL 2 MnCl2 ]·H2 O (3 ) and [CuL 3 MnCl2 ] (4 ) have been synthesized with MnCl2 ·4H2 O. The tetranuclear (1 ) and trinuclear (2 ) complexes were prepared by varying the ratio of the metalloligand [CuL 1 ] and MnCl2 whereas dinuclear complexes3 and4 are the sole products irrespective of the metalloligand : MnCl2 ratio. All the complexes1–4 were structurally characterized by single crystal X-ray diffraction. The tetranuclear (CuII2MnII2) structure of1 is formed by the dimerization of phenoxido bridged Cu II Mn II units whereas the bent CuII2Mn II trinuclear species2 is formed by the coordination of two metalloligands (CuL 1 ) to Mn(ii ) via a diphenoxido bridge. Complexes3 and4 possess a similar dinuclear Cu II Mn II structure in which two phenoxido groups form a bridge between the two metal centres. The variable temperature dc magnetic susceptibility measurements reveal that the Cu(ii ) and Mn(ii ) ions are antiferromagnetically coupled in all the complexes, 1–4 . The values of exchange coupling constants ( J Mn–Cu ) are −45.54, −39.66, −71.54 and −48.40 cm −1 for complexes1–4, respectively. A DFT study of all the complexes has also been performed to rationalize the experimental results of magnetic measurements.